2009
DOI: 10.1017/s1092852900020113
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Gambling Among Racial and Ethnic Groups in the US: Results From the National Epidemiologic Survey on Alcohol and Related Conditions

Abstract: Introduction Prior research suggests that racial minority groups in the US are more vulnerable to develop a gambling disorder than Whites. However, no national survey on gambling disorders exists that has focused on ethnic differences. Methods Analyses of this study were based on the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), a large (n=43,093) nationally representative survey of the adult (18+ years) population residing in households during 2001–2002 period. DSM-IV diagnoses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
110
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 85 publications
12
110
6
Order By: Relevance
“…Gambling disproportionally affects vulnerable populations, such as racial minorities and the economically disadvantaged (Alegria et al 2009;Welte et al 2001). That is, despite similar, or at times less, gambling participation, individuals from racial minorities or from a lower socioeconomic status tend to wage bets more heavily (Welte et al 2006) and therefore experience more adverse effects (Welte et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gambling disproportionally affects vulnerable populations, such as racial minorities and the economically disadvantaged (Alegria et al 2009;Welte et al 2001). That is, despite similar, or at times less, gambling participation, individuals from racial minorities or from a lower socioeconomic status tend to wage bets more heavily (Welte et al 2006) and therefore experience more adverse effects (Welte et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in two studies of Southeast Asians, lifetime problem/ pathological gambling fluctuated from 59% in a convenience sample (Petry et al 2003) to 13.9% in a representative sample (Marshall et al 2009). In the national level data, Asian Americans made up a minuscule portion of the sample (1.7%) (Welte et al 2001), or were combined with Native Americans to form a meaningful comparison group (Alegria et al 2009). In addition, gambling behaviors vary considerably across Asian American ethnic groups (Thomas and Yamine 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Among the general United States population, the percentage of disordered gamblers is higher among blacks and Native Americans (Alegria et al, 2009), and among young adults, studies have suggested that minority groups are more likely to gamble than their white counterparts (Barnes et al, 2010;Rinker, Rodriguez, Krieger, Tackett, & Neighbors, 2016;Stinchfield, 2000). Therefore, more attention to cultural inclusiveness and diversity regarding health communication materials is needed to improve effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Alegría et al (2009) conducted a study based on the national epidemiologic survey on alcohol and related conditions (NESARC; Grant et al 2003). The NESARC is a nationally representative sample from the United States, and for this study included a total of 43,093 individuals aged 18 years and older.…”
Section: Introductionmentioning
confidence: 99%
“…The NESARC is a nationally representative sample from the United States, and for this study included a total of 43,093 individuals aged 18 years and older. The individuals who indicated having gambled five or more times in a 1-year period of their lives (N = 11,153) were asked about the symptoms of DSM-IV (American Psychiatric Association 1994) pathological gambling (Alegría et al 2009). …”
Section: Introductionmentioning
confidence: 99%